Performance Analysis of C23-L54 Series DC Motors in K3 System Using LQR Tracking Controller for Improved Operational Efficiency and Safety - Muhammad Iham Fatqurrochman; Dimas Eka Saputra; Anggara Trisna Nugraha (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Perkapalan Negeri Surabaya, 2025)
Rapid technological advances have had a significant impact in various fields, including occupational safety and health (OSH). In industrial operations, electric motors play an important role in supporting work efficiency and safety. This study aims to analyze the performance of DC motors C23-L54 Series using Linear Quadratic Regulator (LQR) and Linear Quadratic Tracker (LQT) controllers to improve operational efficiency and safety in K3-based systems. Modeling is carried out using a state-space approach, which allows for complex analysis of the input-output relationship of the control system. The simulation was conducted through MATLAB Simulink R2018a with a voltage input of 0.5 V. Initial simulation results show that the unmanned system experiences large oscillations and instability, which has the potential to increase the risk of operational failure and harm to workers. To solve this problem, LQR and LQT controllers are designed to stabilize the system and eliminate oscillations, both in no-noise and noisy conditions. The test was carried out on the mathematical model of order 1 and order 2 using step signals with setpoint values of 0.848 and 0.01905. The results show that the designed controller is able to significantly improve the stability of the system, thereby reducing the risk of device damage and potential work accidents. These findings make a significant contribution to the integration of advanced control technologies to support occupational safety in industrial environments. This research is expected to be a reference in the development of safe and efficient electric motor-based systems.